Displacement washing of spruce pulp with different delignification degree - Rahman, Md. Mostafizur (Univerzita Pardubice, 2019)
The primary goal of the dissertation was to investigate the influence of the degree of delignification of kraft spruce pulp cooked on seven different kappa numbers in the range from 18.1 to 50.1 upon the efficiency of displacement washing under laboratory conditions. The results obtained showed that both the washing yield and the bed efficiency increase with increasing the Péclet and kappa numbers. Washing also reduced the kappa number and the residual lignin content in the pulp fibres. The secondary objective was to monitor the influence of pulp consistency and the wash water temperature on the washing efficiency. The sulphite pulp was also washed and the results were compared with those for the kraft spruce pulp. The results obtained showed that sulphite pulp is better washable comparing to kraft pulp.
Vytěsňovací praní smrkové buničiny o různém stupni delignifikace
Keywords: sulfátová smrková buničina; vytěsňovací praní; prací výtěžek; účinnost praní; zbytkový lignin; sulfitová buničina; kraft spruce pulp; displacement washing; wash yield; bed efficiency; residual lignin; sulphite pulp